"Lost in the noise": DIY amateur music practice in a digital age - Murphy, Michaela (2017)
A fast expanding network of DIY music communities in the UK see digital technologies transforming ways in which part-time amateur musicians are able to collaborate creatively and form alliances, touring and distributing their music to an international audience and expanding the possibilities of a DIY approach to music making beyond its subcultural, micro-cultural past. Creative autonomy and control is sought to be retained and celebrated in shared non- commercial spaces run by the artists themselves. With an interview based approach, this thesis explores the continued importance of gaining a local audience in a digital age, exploring amateur music activities in two very distinct cities. These reveal how local traditions of amateur practice continue to influence musicians and their shared venues, both in their revival and reinvention. How DIY is defined in a digital age is also explored with both observation and interview data revealing the continued legacy of Punk and how this plays a part in DIY’s expanding definition. The approaches and motivations behind amateur musicians seeking out and establishing shared places for their DIY practice reveals a collective striving for creative control and the creative reimagining of disused urban spaces. Whilst there is a commitment to the upkeep of these spaces, there are also essential online activities shared by the amateur musicians that assist their own personal music promotion alongside the networking and expanding of the local DIY communities. This discussion also reveals how the musicians tackle periods of isolation from their peers, as increased opportunities to collaborate remotely with others changes the dynamics of bands and music scenes. In a combining of interview and observational data, the thesis also explores in depth the handcrafting and DIY activities practiced and celebrated in the shared DIY spaces. There is then further discussion as to how the musicians manage their peer networks and how they stay connected to other musicians in their local areas. This reveals more relaxed, open networking tactics widely adopted by amateur musicians in a digital age. There is a continued discussion then as to how the musicians are able to sustain their DIY practices on a part- time basis, with a focus on the co-operative strategies for creating a sense of community, shared values and ambitions amongst the musicians. In conclusion, I draw upon the themes of material, digital, local and global practices, revealing how amateurs seek to protect both a micro-scale, exclusive aspect to their music and opportunities for face-to-face live performance for real engagement with their peers and audiences.